Ansiedad y depresión en pacientes con Diabetes Mellitus tipo 2 que acuden al Centro de Salud de Miraflores- Loja - Gabriela Cecibel Luzuriaga Abad (2023)
Anxiety and depression are pathologies that over the years and each in its own way, affecting millions of people. Patients with Diabetes Mellitus are more likely to have emotional disorders generating considerable effects on their health and socioeconomic consequences, Therefore, the present investigation had the objective of identifying anxiety and depression in patients with Diabetes Mellitus type 2 who come to Miraflores-Loja Health Center. The study had a quantitative, descriptive, relational and prospective approach, with a non-probabilistic sample of 69 patients who came for consultation at Miraflores Health Center and who met the inclusion criteria, obtaining the following results: the prevalence of Diabetes Mellitus type 2 was 2.69%. Using the Hospital Anxiety and Depression Scale (HADS) it was obtained that the incidence in the sex was 56.25% (n=27) anxiety and 43.75% (n=21) depression, in the male sex 100% (n=21) anxiety and 23.81% (n=5) depression, regarding the age group the 40-50 years old, anxiety was evidenced in 92.59% (n=25) and depression in the group of older 50 years old with 66.67% (n=18); in the marital status of widowers 85% (n=17) had anxiety and depression 60% (n=12). In addition, when variables were analyzed using Pearson's Chi-Square statistical association test, a statistically significant relationship Chi2=24.20 (CI 0.95) was obtained, therefore, it is concluded that patients with type 2 Diabetes Mellitus tend to have behaviors emotional